Long-term changes in physical capacity after colorectal cancer treatment. Issue 2 (March 2015) - Hamaker, Marije E.; Prins, Meike C.; Schiphorst, Anandi H.; van Tuyl, Sebastiaan A.C.; Pronk, Apollo; van den Bos, Frederiek
Abstract Older patients with colorectal cancer are faced with the dilemma of choosing between the short-term risks of treatment and the long-term risks of insufficiently treated disease. In addition to treatment-related morbidity and mortality, patients may suffer from loss of physical capacity. The purpose of this review was to gather all available evidence regarding long-term changes in physical functioning and role functioning after colorectal cancer treatment, by performing a systematic Medline and Embase search. This search yielded 27 publications from 23 studies. In 16 studies addressing physical functioning after rectal cancer treatment, a median drop of 10% (range − 26% to − 5%) in the mean score for this item at three months. At six months, mean score was still 7% lower than baseline (range − 18% to 0%) and at twelve months 5% lower (range − 13% to + 5%). For role functioning (i.e. ability to perform daily activities) after rectal cancer treatment, scores were − 18% (range − 39% to − 2%), − 8% (range − 23% to + 6%) and − 5% (range − 17% to + 10%) respectively. Elderly patients experience the greatest and most persistent decline in self-care capacity (up to 61% at one year). This systematic review demonstrates that both physical functioning and role functioning are significantly affected by colorectal cancer surgery. Although initial losses are recovered partially during follow-up, there is a permanent loss in both aspects of physical capacity, in patients of all ages but especially in the elderly. This aspect should be included in patient counselling regarding surgery.